Comparing Platform "Ranking Cultures" Across Languages: The Case of Islam on YouTube in Scandinavia. (January 2019) - Moe, Hallvard
This article is concerned with how different agencies play out in shaping public debate online and, for this purpose, employs an approach that acknowledges the role not just of algorithms seen in isolation, but in context with users. The empirical case is YouTube video search results related to Islam in Danish, Norwegian, and Swedish. As such, the article makes a contribution by adding a comparative layer to the discussion of "ranking cultures, " which has so far focused on individual cases or English-language searches. The analysis is based on a mapping of the highest-ranking videos, as well as a qualitative exploration of these videos' content and context. Findings illustrate how intricate practices of re-posting and re-framing of videos is key to understand the ways YouTube's search function contributes to shape the public image of an issue differently in different language areas and social settings. Findings are related to previous studies of immigration coverage in mainstream news media in the case countries. The discussion highlights the merits of the approach, not only for bringing out nuances in how YouTube shape political issues in different contexts but also for pointing to questions of the broader public debate.